1992
DOI: 10.1677/joe.0.1350333
|View full text |Cite
|
Sign up to set email alerts
|

A polyclonal antibody to the rat oestrogen receptor expressed in Escherichia coli: characterization and application to immunohistochemistry

Abstract: A rat oestrogen receptor-beta-galactosidase fusion protein was expressed using a pEX2/rat oestrogen receptor cDNA construct. Scatchard analysis of [3H]oestradiol-17 beta binding to the cell lysate revealed that the fusion protein had functional binding sites specific for oestradiol with a dissociation constant of 1.49 nmol/l. The relative molecular weight (M(r)) of the fusion protein was determined as 180,000 by immunoblot analysis of the cell lysate employing a monoclonal antibody to the human oestrogen recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
47
0

Year Published

1993
1993
2006
2006

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 0 publications
5
47
0
Order By: Relevance
“…Sen et al (23) have reported that, in the female rat anterior pituitary gland at proestrus, both the concentration of unoccupied and occupied ER and the total estradiol binding in the cytosol decreased markedly with a concomitant marked increase in the concentration of ER in the cell nucleus, to which it was translocated from the cytosol as an ER-estradiol complex. In this experiment, we detected all of the ER in a section, since the polyclonal antibody against rat ER we used is able to react with both forms of the receptor molecule, whether unoccupied or occupied by estradiol (21). The present data supported the study by Sen et al (23) and revealed that the high ER level was due to an increase in that of gonadotrophs and lactotrophs.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Sen et al (23) have reported that, in the female rat anterior pituitary gland at proestrus, both the concentration of unoccupied and occupied ER and the total estradiol binding in the cytosol decreased markedly with a concomitant marked increase in the concentration of ER in the cell nucleus, to which it was translocated from the cytosol as an ER-estradiol complex. In this experiment, we detected all of the ER in a section, since the polyclonal antibody against rat ER we used is able to react with both forms of the receptor molecule, whether unoccupied or occupied by estradiol (21). The present data supported the study by Sen et al (23) and revealed that the high ER level was due to an increase in that of gonadotrophs and lactotrophs.…”
Section: Discussionsupporting
confidence: 89%
“…However, this rat monoclonal antibody may not be suitable for detecting ER in rat organs, as it produces widespread background staining (3). More recently, Okamura et al (21) produced a highly specific polyclonal antiserum against ER expressed in Escherichia coli by utilizing the cDNA which encodes the B-through F-domains of the full length of the rat ER protein (15), and demonstrated the ER in the rat brain (5, 21, 32) and pituitary (21). However, cellular identification of ER-bearing pituitary parenchymal cells has not yet been done with the antiserum.…”
mentioning
confidence: 99%
“…Using immunoblot analysis, the characterization and specificity of the rabbit antiserum against rat ERa used in the present study have been previously described (Okamura et al 1992). Specifically, immunocytochemistry recognizes ERa in the pituitary and neurons in specific brain regions (Okamura et al 1992(Okamura et al , 1994.…”
Section: Discussionmentioning
confidence: 99%
“…Rats were OVX under ether anesthesia to eliminate endogenous estrogens. The antibody used in this study has been reported to recognize both occupied and unoccupied ERa (Okamura et al 1992). However, one study using the same antibody shows a downregulation of ERa expression in the presence of estrogen (Okamura et al 1994).…”
Section: Animals and Treatmentsmentioning
confidence: 92%
See 1 more Smart Citation